The cultivation of students' creativity through the theater extracurricular program in primary school level - Syarif Hidayat; Suciati Nur (Universitas Pendidikan Indonesia, 2021)
Extracurricular activities play an important role in character education, especially the character of student creativity. There are several types of extracurricular; and drama or theater is an alternative extracurricular program that can foster student creativity. Drama or theater activities can facilitate students to develop their creativity in work. The students can express themselves through acting, dancing, playing musical instruments, script writing, and craft making. In the context of education, the character education is needed to instill students' creative attitudes. However, the space to create creative ideas for students is still limited. Therefore, the theater extracurricular activities provide space for students to cultivate their creativity. This study aims to reveal implementation, planning, operation, evaluation, support, and educational barriers to the character education of students' creativity by the theater extracurricular. Exposing qualitative approach, this research reveals the phenomenon of student creativity cultivation by means of theater extracurricular activity in primary school level. The data were revealed through observation, interviews, and documentation. Subsequently, the data was analyzed by using descriptive qualitative analysis with three stages: data reduction, data display, and data verification. Based on the interpretation of the results, students' creativity is grown and developed optimally through the theater extracurricular with 4P (personal, push, process, product) strategy and peer tutor method. Still, there is lack of appreciation of the school to the students' work and facilities that need to be updated and equipped.